Organizational Influences and Quality-of-Life Issues During the Professional Socialization of Certified Athletic Trainers Working in the National Collegiate Athletic Association Division I Setting - Pitney, William A (National Athletic Trainers Association, 2006)
Context: Health professionals are exposed to critical influences and pressures when socialized into their work environments. Little is known about the organizational socialization of certified athletic trainers (ATs) in the collegiate context. Objective: To discuss the organizational influences and quality-of-life issues as each relates to the professional socialization of ATs working in the National Collegiate Athletic Association Division I setting. Design: A qualitative design of in-depth interviews and follow-up electronic interviews was used to examine the organizational socialization of ATs. Setting: Participants associated with Division I athletic programs from 4 National Athletic Trainers' Association districts volunteered for the study. Participants: A total of 11 men and 5 women participated in the study, consisting of 14 ATs and 2 athletic directors. Data Collection and Analysis: Interviews were transcribed verbatim and analyzed inductively. A peer review, member checks, and data source triangulation were performed to establish trustworthiness. Results: Two categories emerged that provide insight into the experiences that affected the professional socialization of the ATs: organizational influences and quality-of-life issues. The data indicate that the participants in this study were heavily influenced by the bureaucratic tendencies of the Division I athletic organizations in which they worked. The participants were extremely concerned about the diminished quality of life that may result from being an AT in this context. They were, however, able to maintain a commitment to delivering quality care to the student-athletes despite these influences. High work volume and low administrative support were commonly cited as problems, thus creating concern about diminished quality of life and the fear of burnout. Conclusions: The AT's role appears not only rewarding but also challenging. The reward is working closely with patients and developing an interpersonal bond; the challenge is dealing with a bureaucratic structure and balancing one's professional and personal lives to prevent burnout. Thought should be given to using intervention strategies to mitigate the negative influences on the AT's role.